Implementasi Perlindungan Hak Konsumen dalam Layanan Go-Food di Kota Makassar: Analisis Mazhab Fikih - Haq, Muhammad Sabilil; Sabir, Muhammad (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
This research discusses "Implementation of Consumer Rights Protection in Go-Food Services in Makassar City (Analysis of the Fikih Mazhab)" which presents two problem formulations, namely: First, How is consumer protection in the regulations contained in the food ordering policy through Go-Food services in Makassar City? Second, What are the views of the 4 Imam Mazhab Fikih on muamalah contracts and consumer protection in Go-Food services in Makassar City? The type of research used by the author in this thesis is empirical juridical legal research using qualitative and normative types of research. This research uses primary research data, namely interviews and observations and uses secondary data in the form of laws and regulations related to Consumer Rights Protection. Journals and other legal websites. The results of this study indicate that: First, Legal Protection of Consumer Rights on Go-Food services (Analysis of fiqh schools and law number 8 of 1999 concerning consumer protection) has been carried out properly in terms of procedures and regulations from Gojek, but in some cases the author has encountered that there are elements either from the driver or the restaurant that cooperates with Gojek but does not heed the regulations that Gojek has set. Second, the opinions of the mazhab scholars regarding the muamalah fikih of online buying and selling, especially in Go-Food transactions applied by Gojek, have been fully approved by the scholars if the transaction does not contain things that do not have certainty or (gharar) and fulfil the rules or Islamic law. The implications of this research, namely related to legal protection of consumer protection rights (analysis of fiqh madhhab and law number 8 of 1999 concerning consumer protection) Consumer rights according to scholars or imam madhhab who all agree on the protection of consumers to protect all the rights of all parties and because it is one of the principles of Islamic law.